On the global reachability of structured 2D state space systems - Pereira, Ricardo (2012)
This paper is a contribution to extend the study of structured dynamical systems to the case of systems evolving over two-dimensional domains, i.e., 2D systems. In particular, we consider 2D Fornasini-Marchesini state space models and obtain necessary and sufficient conditions for structured global reachability. Such conditions are stated in terms of the generic rank and the irreducibility of suitably defined matrices and generalize well known results on the reachability of 1D structured systems.